Oak Wilt: A Potential Future Threat to Oaks in Florida - Kelly Peacock; Jason Smith (EDIS)
FOR274, a 5-page fact sheet by Kelly Peacock and Jason Smith, provides information on the diagnosis, biology, and management of the disease and should provide guidance for future efforts to identify and manage oak wilt in the state of Florida. Includes references. Published by the UF Department of School of Forest Resources and Conservation, November 2010. Reviewed November 2013.